The Effectiveness of The Posyandu and Its Relation to Leadership and Management - Maryati, Husnah; Permanasari, Vetty Yulianty (Journal of Indonesian Health Policy and Administration, 2016)
Data on infant mortality in the city of Bogor has increased from 26 to be 62 cases in 2013. Posyandu is one of the facility in a society that runs the health program where one goal is carrying out activities to accelerate the decline in the death rate of mothers and babies. The problems at posyandu in Bogor is the number of active cadres continue to decline while cadre recruitment insufficient, and less active of the function of The National Working team of posyandu. The report of newborn deaths by 2013 and 2014 stated that more than half (55 and 52.7 percent) posyandu where there were cases of infant death were posyandu at first and medium development level. This research would like to see how the effectiveness of the leadership factor (communication, competence), management functions (planning, organizing, implementing and controlling), work environment (system support, availability, the availability of means of support and incentives) as well as the characteristics of respondents (posyandu classification, age, number of years served and the work) to mass based activities (UKBM) in Posyandu. We used a cross sectional design. About 70 posyandu chairman cadres as the respondents. This research resulted in the most decisive factor, namely the competence of the chairman of cadres. Knowledge and competence of cadres is already good and should continue to be maintained. The Division of duties and authorities which are clearly made in the region of posyandu organization Bogor City is already good (average rating scale 6.19). The strength of leadership and good management at the operational level of posyandu makes posyandu is more effective in achieving the objectives. There is a relationship between variables, functions, management leadership, the working environment and the characteristics of the respondents against the effectiveness of the posyandu. Data on infant mortality in the city of Bogor has increased from 26 to be 62 cases in 2013. Posyandu is one of the facility in a society that runs the health program where one goal is carrying out activities to accelerate the decline in the death rate of mothers and babies. The problems at posyandu in Bogor is the number of active cadres continue to decline while cadre recruitment insufficient, and less active of the function of The National Working team of posyandu. The report of newborn deaths by 2013 and 2014 stated that more than half (55 and 52.7 percent) posyandu where there were cases of infant death were posyandu at first and medium development level. This research would like to see how the effectiveness of the leadership factor (communication, competence), management functions (planning, organizing, implementing and controlling), work environment (system support, availability, the availability of means of support and incentives) as well as the characteristics of respondents (posyandu classification, age, number of years served and the work) to mass based activities (UKBM) in Posyandu. We used a cross sectional design. About 70 posyandu chairman cadres as the respondents. This research resulted in the most decisive factor, namely the competence of the chairman of cadres. Knowledge and competence of cadres is already good and should continue to be maintained. The Division of duties and authorities which are clearly made in the region of posyandu organization Bogor City is already good (average rating scale 6.19). The strength of leadership and good management at the operational level of posyandu makes posyandu is more effective in achieving the objectives. There is a relationship between variables, functions, management leadership, the working environment and the characteristics of the respondents against the effectiveness of the posyandu.